Hubungan Dukungan Suami dengan Tingkat Kecemasan Ibu Hamil Trimester III dalam Menghadapi Persalinan - Septia, Cheeqa Mardevi; arneti, Arneti; Khadijah, Siti (Jurusan Kebidanan Poltekkes Kemenkes Padang, 2024)
Anxiety is an emotional condition characterized by feelings of worry or fear without a clear cause and is commonly experienced by pregnant women, especially in the third trimester. Anxiety during pregnancy can negatively affect maternal and fetal health, increasing the risk of pregnancy complications, impaired fetal development, and difficult labor. The World Health Organization (WHO) reported that approximately 15% of pregnant women experience anxiety, which may increase to 30% in first pregnancies. In Indonesia, the prevalence of anxiety among pregnant women is 28.7%, while in Sumatra it reaches 52.35%. Data from Baso Public Health Center in 2024 showed that 40% of third-trimester pregnant women experienced anxiety symptoms. One important factor influencing maternal anxiety is husband’s support. This study aimed to determine the relationship between husband’s support and anxiety levels among third-trimester pregnant women at Baso Public Health Center in 2025. This study used a quantitative cross-sectional design involving 30 third-trimester pregnant women selected through total sampling. Data were collected using a husband’s support questionnaire and the Hamilton Anxiety Rating Scale (HARS) and analyzed using Chi-square tests. The results showed that 56.7% of respondents did not experience anxiety and 53.3% received husband’s support. A significant relationship was found between husband’s support and anxiety levels (p = 0.001).